Peningkatan Ekonomi Rumah Tangga Melalui Pelatihan Pembuatabn Boneka Jari Bagi Wali Murid RAUDLATUL ATHFAL (RA) AL JIHAD Kelurahan Bunulrejo Kecamatan Blimbing - Cristiana Normalita de Lima; Tini Adiatma; Beatus Tambaip (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2022)
Early Childhood Education (PAUD) is a level of education prior to basic education which is a coaching effort aimed at children from birth up to the age of six which is carried out through the provision of educational stimuli to help physical and spiritual growth and development so that children have readiness in entering further education. 3 Education for early childhood is exploring direct experiences experienced by children through optimizing their five senses. The service is carried out to improve the household economy of the surrounding community who are given training Dolls are made with simple tools such as bottle caps, ping pong balls, and small bamboo which can be used as doll heads. As the name implies, this doll is played using the fingers. The head of the doll is placed on our fingertips / inside. It can also be made from a kind of glove, where at the fingertips the glove is already in the shape of a doll's head and thus we just have to play with it. The development of language or communication in children is one aspect of the stages of child development that should be of concern to educators and parents. Soetjiningsih revealed that children are born with mechanisms and abilities to develop speech and language skills. Language development is the child's ability to respond to sounds, follow directions and speak spontaneously. Wong stated that the rate of speech development in children varies from one child to another and is related to the neurological system and cognitive development